(untitled) (Bangladesh Journal of Animal Science, 2024)
The experiment was conducted to compare the effect of different sources of lysine on growth performance, carcass yields and serum biochemical parameters in broiler. A total of 400 Arbor Acres straight run chicks were randomly assigned into 4 different treatment groups for five weeks. The treatment groups were; T1 (100% Ajinomoto lysine), T2 (100% CJ lysine), T3(100% Natural lysine) and T4(50% Ajinomoto + 50% Natural lysine). Each treatment consisted of four replicates and of each 25 chicks. Throughout the experiment body weight, body weight gain, feed intake and feed conversion ratio were recorded as growth performance. Carcass characteristics and blood biochemical profile were also taken after the end of feeding trial. The supplementation of different sources of lysine with feed had significant (P<0.05) effect on growth performances. Results showed that CJ lysine treated broilers had significantly (P<0.05) higher body weight and body weight gain at the end of the experiment compared to Ajinomoto and Natural lysine treated groups. FCR was improved significantly (P<0.05) in CJ lysine group (1.56) compare to the Ajinomoto group (1.69) and Natural lysine group (1.68). Abdominal fat weight showed significant (P<0.05) variation among different treatment groups. Based on the results of this study, it may be concluded that the supplementation of Ajinomoto lysine, CJ lysine and Natural lysine with feed could improve growth performance of broiler and CJ lysine could be considered as performance enhancer in broiler production. Bangladesh Journal of Animal Science 53 (2): 68-76, 2024